Implementasi Metode Pengembangan Sistem Prototype pada Rancang Bangun Aplikasi Marketplace Lensa Buana - Reynard Adelard; Richo Muthicahya; Evan Setiawan Wicaksono; Laurentius Kenneth V; Siska Narulita; Sekarlangit (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
In line with the development of the digital potential of the creative economy, the demand for quality visual content from photography and videography industry players has also increased. However, access to quality photographers and videographers is still a problem for some people. Likewise, photographers and videographers also experience difficulties in getting clients. Photographers and videographers feel that the use of social media has not been maximized in helping them get clients. In addition to these problems, these photographers and videographers also have difficulty in disseminating the events held. To overcome this problem, researchers developed a digital platform that can accommodate the interests of photography and videography service providers, as well as the community of users of these services. The digital platform developed by researchers is named the “Lensa Buana” marketplace application. The development of the Lensa Buana marketplace application uses the prototype system development method. With this application, it is hoped that photography and videography service providers can reach more consumers, while the community as consumers can easily get photography and videography services according to their needs and desired quality.